Analysis of Students' Motivation in Learning Chemistry: Descriptive and Comparative Studies - Saputri, Utari Aulia Tianda; Pranata, Ogi Danika; Zebua, Dinyah Rizki Yanti (JURNAL PENDIDIKAN SAINS (JPS), 2025)
The aim of this research is to analyze the motivation of high school students in learning chemistry, investigating its determinants and inter-school differences. Using a quantitative descriptive and comparative approach, data were collected from 207 students across two high schools via a motivation questionnaire, with 156 valid responses retained for analysis. Results revealed a moderate overall level of motivation, with self-efficacy, active learning strategies, and achievement goals emerging as significant factors. Comparative analyses indicated differences in self-efficacy and performance goals between the two schools. The findings underscore the importance of understanding students' motivation in chemistry learning and its implications for educational practice. Future research could explore contextual and longitudinal influences on motivation, informing evidence-based interventions to enhance students' learning experiences and outcomes. This study contributes to the literature on student motivation in science education and provides insights for educators, policymakers, and researchers seeking to promote student engagement and achievement in chemistry.